Pergeseran Bahasa Tetun Fehan dalam Ranah Keluarga pada Guyub Tutur Masyarakat Belu di Wilayah di Wilayah Perbatasan RI - RDTL - Ate, Christmas Prasetia; Ndapa Lawa, Selfiana T. M. (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
This research aims to identify the pattern of language shift in Tetun Fehan language and the influencing factors in the speech community in Belu, RI - RDTL border area. This research uses a sociolinguistic approach by applying a qualitative descriptive method. The research subjects were 37 head of families which include 110 speakers of Tetun Fehan language. The process of collecting data through observation and interviews. The collected data is then processed in three stages, namely classification, interpretation and data analysis which is displayed in the form of descriptive narrative. The results indicates there is a language shift in the family realm with the pattern of communication relationships between husband to wife, wife to husband, parent to children and children to parent. The factors that influence the language shift come from internal factor, includes (1) the lack of use of the Tetun Fehan language (2) the reluctance to use the language (3) the lack of socialization in the family and (4) interaction with surrounding, and external factors includes (1) education factor (2) migration factor).Keywords: Tetun Fehan language, language shift, speech community, border area